PENGARUH DUKUNGAN ORGANISASI DAN JOB EMBEDDEDNESS TERHADAP KINERJA KARYAWAN PT. SATYA MANDALA PRATAMA - Noviansyah Noviansyah; Hilmi Wiranawata; Linda Kurniawati (Ekonomika, 2023)
The data analysis technique used is Multiple Linear Regression. Based on theresults of data processing, it was found that the results of the partial analysis oforganizational support variables had a t-count value (12.813) > t-table (2.01290),then Ho was rejected and Ha was accepted. This means that there is an influenceof Organizational Support on the performance of employees of PT. SatyaMandala Pratama, while the job embeddedness variable has a value of t-count(4.214) > t-table (2.01290) then Ho was rejected and Ha was accepted. Thismeans that there is an influence of Job Embeddedness on the performance ofemployees of PT. Satya Mandala Pratama. Simultaneously F count 286,630>Ftable 3.20 then Ho was rejected and Ha was accepted, meaning thatsimultaneously there is a significant influence of Organizational Support and JobEmbeddedness on the performance of employees of PT. Satya Mandala Pratama.The coefficient of determination (R2) obtained is 0.926. This shows that thecontribution of Organizational Support and Job Embeddedness to employees’performance is 92.6% while the remaining 7.4% is influenced by other variablesnot included in this research model such as abilities and expertise (Kasmir,2016:189-193).